Family Factors and Their Effects on Child Violent Behavior - Peovska, Natasha (Kriminalističke teme, 2022)
The results from recent criminological research in the field of juvenile delinquency, address the family as an important factor that can influence on the children violent behavior. According to these findings, this paper will elaborate and analyze part of family characteristics that can influence, as a risk factors for children violent behavior. There are many characteristics that are related to the family which can be put in some correlation with the violent behavior of the child. Thus, the way the family function, the relationships that exist between family members, the size of the family, but also the circumstances in which family lives (especially economic circumstances) can further deepen or emphasize the negative individual characteristics of children. The upbringing style, the lack of attention, parental rejection, parental indulgence, negligence, the violent behavior in the home (physical and verbal aggression between parents and parent towards a child), increases the likelihood of negative behavior in children. In addition to the above-mentioned factors, based on a research review on child aggressive behavior, it has been concluded that the absence of a father, loss of a parent through divorce or death are factors that also can be associated with childhood aggression. Among the important family factors that will also be analyzed in this paper are the presence of alcoholism, criminal, and aggressive behavior in the family.